Prevalence of multidrug resistance in human pathogenic Staphylococcus aureus and their sensitivity to Allamanda cathartica L. leaf extract - Chowdhury, Md. Al Nayem; Hossain, Md. Nazmul; Rahman, Md. Mahbubur; Ashrafuzzaman, Md. (International Current Pharmaceutical Journal, 2013)
Staphylococcus aureus is one of the major pathogen responsible for skin infection, urinary tract infection (UTI) and endocarditis in human. The study was performed to determine the prevalence of multidrug resistant S. aureus in human clinical sample and to evaluate their sensitivity to Allamanda cathartica L. leaf extract. A total of 12 isolates were identified belongs to S. aureus by performing several physiological and biochemical tests. The isolates exhibited highest resistant (75%) to streptomycin and lowest (33.33%) against co-trimoxazole followed by disc diffusion assay of eight antibiotics tested. The other four antibiotics such as azithromycin, chloramphenicol, gentamycin and erythromycin exhibited 50 to 66.67% resistant to present isolates. Here we found that 75% of S. aureus isolates were multidrug-resistant (MDR). The crude leaf extract of A. cathartica L. found to possess antibacterial properties at the rate of 83.33% against S. aureus isolates with 12-22 mm zone of inhibition. Results of TLC states that Benzene : Ethyl acetate (1:1) solvent system was more effective for initial separation of compound from crude leaf extract resulted three distinct bands with different Rf values ranging from 0.53 to 0.89. The result of this study refers that A. cathartica L. leaf extract would be useful to develop effective drugs that would reduce the higher prevalence of multidrug resistance S. aureus causing clinical infection in human. DOI: http://dx.doi.org/10.3329/icpj.v2i11.16525 International Current Pharmaceutical Journal, October 2013, 2(11): 185-188